Items for measuring the construct of Workplace Oral Communication Skills (WOCS) amongst civil engineering students: step by step using Exploratory Factor Analysis (EFA) - Masduki, Masadliahani; Zakaria, Normah (PERTANIKA Universiti Putra Malaysia Press, 2022)
One of the most crucial factors that influence the success of a construction project is communication. However, past studies found that communication failure frequently occurs at civil engineering workplaces. Among communication failures reported were oral communications, such as giving instruction and briefing; skills, which are supposed to be mastered by engineering graduates during their study years. Thus, students need to equip themselves with proper oral communication skills before they enter the industry. As such, this study aimed to develop a valid and reliable survey instrument to measure Workplace Oral Communication Skills (WOCS) by performing a step-by-step instrument validation through exploratory factor analysis (EFA). The questionnaire consisted of nine components, with 39 items of Workplace Oral Communication Skills (WOCS). In the study, the EFA was carried out in three rotations until every item’s factor loading met the minimum requirement of 0.60. Notably, Bartlett’s test of Sphericity was significant (p <0.05), and the Kaiser-Meyer-Olkin test was more than 0.60 in every rotation, which means that the sample size was adequate. Furthermore, all components showed a Cronbach Alpha >0.70, which indicates that the instrument is reliable. The final result of the EFA showed that the WOCS construct only had six components with 25 items. Therefore, this study had managed to validate the instrument. Thus, Confirmatory Factor Analysis (CFA) can proceed in the next study using the validated instrument.